The relationship of anxiety emotional intelligence and concentration of thinking to the decision-making ability of football referees - Hamzah, M Alif; Hartono, Mugiyo; Nasuka, Nasuka (Journal Of Sport Education (JOPE), 2024)
(Indonesian)Penelitian ini bertujuan untuk mengetahui hubungan antara kecemasan, kecerdasan emosional, dan konsentrasi berpikir dengan pengambilan keputusan wasit sepak bola di Kabupaten Aceh Besar. Penelitian ini mengadopsi pendekatan kuantitatif dengan metode deskriptif korelasional. Populasi yang menjadi fokus penelitian ini adalah wasit sepak bola di Kabupaten Aceh Besar, yang berjumlah 55 orang. Teknik sampling yang digunakan adalah Total Sampling. Hasil penelitian 1) Hubungan antara Kecemasan Terhadap Pengambilan Keputusan Wasit Sepakbola dengan Hasil Fhitung 24,522> Ftabel 4,02, 2) Hubungan antara Kecerdasan Emosil Terhadap Pengambilan Keputusan Wasit Sepakbola dengan Hasil Fhitung 17,977 > Ftabel 4,02, 3) Hubungan antara Konsentrasi Berfikir Terhadap Pengambilan Keputusan Wasit Sepakbola dengan Hasil Fhitung 15,858 > Ftabel 4,02, 4) Hubungan antara Kecemasan, Kecerdasan Emosional dan Konsentrasi Berfikir Terhadap Pengambilan Keputusan Wasit Sepakbola dengan Hasil Fhitung 28,356 > Ftabel 2,79. Kesimpulannya adalah terdapat hubungan signifikan antara tingkat kecemasan dan pengambilan keputusan wasit sepakbola, terdapat hubungan signifikan antara tingkat kecerdasan emosional dan pengambilan keputusan wasit sepakbola, terdapat hubungan signifikan antara tingkat konsentrasi berpikir dan pengambilan keputusan wasit sepakbola, terdapat hubungan signifikan antara tingkat kecemasan, kecerdasan emosional, dan konsentrasi berpikir dengan pengambilan keputusan wasit sepakbola Kabupaten Aceh Besar.(English)This study aims to determine the relationship between anxiety, emotional intelligence, and concentration of thinking with the decision-making of football referees in Aceh Besar Regency. This study adopts a quantitative approach with a correlational descriptive method. The population that was the focus of this study was football referees in Aceh Besar Regency, which amounted to 55 people. The sampling technique used is Total Sampling. The results of the study 1) The Relationship between Anxiety About Football Referee Decision Making with Fcount Results 24.522> Ftable 4.02, 2) The Relationship between Emotional Intelligence on Football Referee Decision Making with Fcount Results 17.977 > Ftable 4.02, 3) The Relationship between Thinking Concentration on Football Referee Decision Making with Fcount Results 15.858 > Ftable 4.02, 4) The Relationship between Anxiety, Emotional Intelligence and Thinking Concentration on Decision Making Football Referee with Fcount results 28.356 > Ftable 2.79. The conclusion is that there is a significant relationship between the level of anxiety and decision making of football referees, there is a significant relationship between the level of emotional intelligence and decision making of football referees, there is a significant relationship between the level of concentration of thinking and decision making of football referees, there is a significant relationship between the level of anxiety, emotional intelligence, and concentration of thinking with the decision making of football referees Aceh Regency Big.Copyright © The Author (s) 2024Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.